Predictors of Knowledge and Attitude Regarding Organ Donation in Kuwait - Bosakhar, Batool Y.; Al-Mesailekh, Zainab A.; Al-Farhan, Shareefah A.; Arab, Danah A.; Al-Tawheid, Nour A.; Al-Ali, Nourah F.; Mitra, Amal K. (IMC Journal of Medical Science, 2017)
Background and objectives: In Kuwait, information regarding public knowledge and attitudes towards organ donation are scanty This study aimed to evaluate public knowledge and attitude regarding organ donation and determine factors which predict them. Methods: This cross-sectional study was conducted among 630 participants recruited from 27 randomly selected public cooperative societies and private supermarkets in Kuwait. A self-administered questionnaire was used to collect data. Results: The prevalence rate of knowledge about organ donation was 68%, with a significantly higher rate among females than males (73% vs. 63%, respectively, p = 0.01). A composite score of knowledge was also higher among females than males (8.4 ± 5.8 vs. 6.8 ± 5.8, respectively, p = 0.001). In multivariate analysis, female gender (OR = 1.7; 95% CI =1.2, 2.4) and an educational level of bachelors degree or higher (OR = 2.6, 95% CI = 1.7, 3.9) were significant predictors of the knowledge. Among the barriers, more females than males mentioned about the fear of the operative procedures (p<0.001) and complications after the surgery (p = 0.011). Overall, 73% accepted the idea of organ donation during life, and 67% actually opted for donating their organs during life. However, almost everybody wanted to donate organs to their relatives. Conclusion: The study identified factors predicting knowledge and attitude regarding organ donation. The results will help in planning how to improve the rate of donors in Kuwait. IMC J Med Sci 2016; 10(1): 01-09